Acetylation of glycerol over carbon supported yttrium oxide catalysts and optimization analysis by response surface methodology - Amadi, Uchenna Fidelis (2022)
The use of homogeneous catalysts in glycerol acetylation have been associated with several shortcomings hence the growing interest in the use of heterogeneous catalysts such as metal oxide. Carbon supported yttrium oxide (Y2O3) catalysts were synthesized via carbonization of palm kernel shell (PKS) and subsequent functionalization with 5wt%, 10wt% and 15wt% yttrium oxide (Y2O3), respectively. The catalysts were also characterized by N2 physisorption analysis (BET surface area), X-ray diffraction (XRD), thermogravimetric analysis (TGA), scanning electron microscopy coupled with energy dispersive X-ray spectroscopy (SEM-EDX), Fourier transform infra-red (FTIR), and temperature programmed desorption-ammonia (TPD-NH3) and tested in glycerol acetylation. The 15wt% Y2O3/PKS-T700 catalyst with the highest potential was used for the optimization reaction using four-factor, two-level face-centred central composite design (24 CCD) of the response surface methodology. The optimized conditions were found to be temperature 130 ℃, glycerol-to-acetic acid molar ratio 1:11 and catalyst loading 0.5 g in 5 h reaction time. Glycerol acetylation reaction revealed optimal results of 99.8% glycerol conversion (GC) and product selectivity of 15.7% monoacetin (MA), 58.8% diacetin (DA), and 29.4% triacetin (TA), respectively. The model terms were found to be significant (p<0.05) with coefficient of determination (R2) close to unity (>0.99) while the predicted R2 and the adjusted R2 were in agreement with each other. The characteristics of the catalyst revealed carbon, hydrogen and yttrium were 71.33%, 15.66% and 13.01%, acid site density of 339.9 μmol/g, while the BET surface area, pore volume and the average pore size were 503 m2/g, 0.452 cm3/g and 2.5 nm. On subjecting the catalyst to reusability study in three (3) reaction cycles under the optimal conditions, the catalyst was found to maintain good reaction with little degradation as observed in the small decline in performance attributed to slight leaching of the active site.